2017
DOI: 10.1515/pjct-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of poly(ε-caprolactone) in natural water environments

Abstract: The environmental degradation of poly(ε-caprolactone) [PCL] in natural fresh water (pond) and in The Baltic Sea is presented in this paper. The characteristic parameters of both environments were measured during experiment and their infl uence on the biodegradation of the samples was discussed. The loss of weight and changes of surface morphology of polymer samples were tested during the period of incubation. The poly(ε-caprolactone) was more biodegradable in natural sea water than in pond. PCL samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 16 publications
0
59
0
Order By: Relevance
“…Degradation of the implanted PCL devices involves hydrolysis of the ester bonds of the polymer chains. 7,[14][15][16][17][18] Hydrolytic degradation is a 2-phase process. In the first phase, by penetrating the polymer bulk, water causes chain scission.…”
Section: Polycaprolactone Is a Well-known Polymer Pcl Possesses Specimentioning
confidence: 99%
“…Degradation of the implanted PCL devices involves hydrolysis of the ester bonds of the polymer chains. 7,[14][15][16][17][18] Hydrolytic degradation is a 2-phase process. In the first phase, by penetrating the polymer bulk, water causes chain scission.…”
Section: Polycaprolactone Is a Well-known Polymer Pcl Possesses Specimentioning
confidence: 99%
“…for polyester biodegradation. However, an increasing number of studies have shown that most polyester‐based materials with good biodegradability in soil do not degrade or degrade very slowly in oceans; these materials include poly(lactic acid), polyhydroxybutyrate, poly(butylene succinate), and polycaprolactone . Oceans are characterized by high‐salt, high‐pressure, low‐temperature environments containing mobile and diluted nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…The melting enthalpy was calculated as the melting peak area surface. The degree of crystallinity (X c ) was calculated according to Eq.1 [26]:…”
Section: Differential Scanning Calorimetry Methodsmentioning
confidence: 99%